2018
DOI: 10.1002/jcc.25582
|View full text |Cite
|
Sign up to set email alerts
|

A Theoretical study on the charge and discharge states of Na‐ion battery cathode material, Na1+xFePO4F

Abstract: Na2FePO4F is a promising cathode material for a Na‐ion battery because of its high electronic capacity and good cycle performance. In this work, first principle calculations combined with cluster expansion and the Monte Carlo method have been applied to analyze the charge and discharge processes of Na2FePO4F by examining the voltage curve and the phase diagram. As a result of the density functional theory calculation and experimental verification with structural analysis, we found that the most stable structur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 36 publications
2
5
0
Order By: Relevance
“…P21/b11 space group (Figure 2). [51] The theoretical calculation results are in good agreement with the previous experimental results.…”
Section: Fluorophosphates (Po 4 -F)supporting
confidence: 87%
See 2 more Smart Citations
“…P21/b11 space group (Figure 2). [51] The theoretical calculation results are in good agreement with the previous experimental results.…”
Section: Fluorophosphates (Po 4 -F)supporting
confidence: 87%
“…[50] Recently, Shinagawa et al applied density functional theory calculation to study the mechanism of Na ion storage, which found a stable intermediate phase of Na 1.5 FePO 4 F with Reproduced with permission. [51] Copyright 2018, Wiley-VCH.…”
Section: Fluorophosphates (Po 4 -F)mentioning
confidence: 99%
See 1 more Smart Citation
“…[ 70 ] The phase transition was found between Na 2 FePO 4 F phase and NaFePO 4 F phase, as illustrated in Figure 10b. Furtherly, Yamashita group [ 71 ] revealed that Na 1.5 FePO 4 F with P 21 /b 11 space group is the only stable intermedia phase by using DFT calculations cooperated with experiment. The above‐mentioned intermedia phase was equally verified utilizing ssNMR (Figure 10c) combined with in situ XRD technology.…”
Section: Mixed‐polyanionsmentioning
confidence: 95%
“…Yamashita group employed first principle calculation along with Monte Carlo method to analyze the (dis)charge mechanism of NFPF. [ 202 ] They found the most stable structure of Na 1.5 FePO 4 F having monoclinic structure (s.g. P 2 1 / b 11). Indeed, structural evolution during (de)insertion in Na 2 FePO 4 F still remains vague warranting further research.…”
Section: Fluorophosphatesmentioning
confidence: 99%